الرفاهية الاجتماعية عند مديري دوائر الدولة - محمد فاطمة صالح; صالح علي عبد الرحيم (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The current research aims to identify the level of social well-being among heads of government departments in Al-Diwaniyah Governorate, and to examine the statistically significant differences in this well-being according to the variables of gender (male, female) and job position (department director, assistant director, section head, division manager). To achieve the objectives of the research, the researcher developed a scale for social well-being based on Keyes’ model (2002). The final version of the scale consisted of 19 items, distributed over six response alternatives. The tool was applied to a randomly selected sample of 300 department heads from 13 institutions in Al-Diwaniyah. The sample included various administrative positions, with males representing 71% and females 29% of the total sample. The results showed that government department managers enjoy a good level of social well-being. No statistically significant differences were found in social well-being based on gender or job position. Based on the results, the researcher presented a set of recommendations and proposals aimed at enhancing social well-being among administrative leadership.